Penerapan Model Quantum Teaching Berbantuan Mind Map Pada Pemahaman Konsep Fisika Siswa Kelas XI IPA MAN Balai Selasa Kab. Pesisir Selatan - Nurhasnah, Nurhasnah (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The purposes of this research to know determine the difference of concept Quantum Teaching assisted by mind map model with the conventional learning of class XI IPA in MAN Balai Selasa. This research uses quasi experiment with randomized control group only design. The population of thisÂ research is the student of class XI IPA which consist ofÂ twoÂ class. The sample of the reseacrh use total sampling technique, XI IPA2 as experiment group and XI IPA1 as control group. The instrumen of this research is tes of concept of learners in the form of essay. The result showed that the average of experimental class was concept of learners 84,95 and control class was 81,30. Data analyzed uses t-test independent with SPSS. The results showed that the quantum teaching assisted by mind map model gave concept comprehension better with t test t count > t table = 1,926> 1,69.